In situ dry matter digestibility of three fattening diets for lambs. - Salinas Chavira, Jaime (2011)
The objective of this work was themeasure the in situ and ruminal degradability and dry matterdigestibility of three fattening diets for lambs, used by lambproducers in the central area of Tamaulipas, México. Thenylon bag technique was used to determine in situ dry matterdigestibility, using three lambs with cannulas in the rumen,distributed in a Latin Square design. The ruminal incubationtimes were 0, 4, 8, 12, 24 and 48 h. All treatment diets (T)used ground sorghum grain (Sorghum vulgare) as a base.T1 included rice (Oryza sativa) polishing with 7.53% on adry matter basis (DM) of sorghum straw as forage; T2 had5% DM of sorghum straw as forage; and T3 had 5% DM ofbuffel grass (Cenchrus ciliaris) hay plus 3% DM of alfalfahay (Medicago sativa). In T1, the highest (P<0.05) value ofdigestibility at 0 and 4 h was observed. For 24 h, the highest(P<0.50) digestible fraction was obtained with T2. At 48 h,no difference (P>0.05) was observed between treatments.The washing loss and the degradation constant were higher(P<0.05) for T1 than T2 and T3. The diet of T1, containingrice polishing, produced the highest digestible fraction atthe fi rst hours of incubation in rumen (0 and 4 h). T3 wasdigested in smaller proportion, although it could be the bestdiet for feedlots of lambs because of the lower acidosis risk.